Subglacial Lake CECs: Discovery and in situ survey of a privileged research site in West Antarctica. Issue 10 (21st May 2015) - Rivera, Andrés; Uribe, José; Zamora, Rodrigo; Oberreuter, Jonathan
Abstract We report the discovery and on‐the‐ground radar mapping of a subglacial lake in Antarctica, that we have named Lake CECs (Centro de Estudios Científicos) in honor of the institute we belong to. It is located in the central part of the West Antarctic Ice Sheet, right underneath the Institute Ice Stream and Minnesota Glacier ice divide, and has not experienced surface elevation changes during the last 10 years. The ratio between the area of the subglacial lake and that of its feeding basin is larger than those for either subglacial lakes Ellsworth or Whillans, and it has a depth comparable to that of Ellsworth and greater than that of Whillans. Its ice thickness is ∼600 m less than that over Ellsworth. The lake is very likely a system with long water residence time. The recent finding of microbial life in Lake Whillans emphasizes the potential of Subglacial Lake CECs for biological exploration.